BRAF status in сito-morphological diagnosis of thyroid nodules - Yu. M. Tarashchenko; A. Ye. Kovalenko; M. V. Ostafiichuk; K. A. Nekrasov (Zaporozhye State Medical University, 2020)
The aim of study - to determine the significance of the BRAF V600E mutation presence in the cytomorphological diagnosis of thyroid nodules. Materials and methods. The study included 65 patients requiring surgical treatment for thyroid nodular pathology. Material to determine the BRAF V600E mutation was taken by means of a fine needle aspiration biopsy before surgery. The BRAF V600E mutation was detected by real-time PCR analysis. Results. A pathomorphological study of the removed thyroid nodules showed that all 22 benign nodules were BRAF-negative. Among the 43 papillary thyroid cancer only 20 were BRAF-positive (46.5 %). BRAF mutations were found more often (P < 0.001) in patients with classical and oxyphilic cell papillary thyroid cancer (60 % and 100 %, respectively) than in patients with follicular variant of PTC (6.7 %). Locally invasive tumors were more often BRAF-negative cases (P < 0.05) than non-invasive tumors and amounted to 75.0 % and 37.5 %, respectively. But, when comparing the morphological variant and invasive properties of the tumor, it was found that all cases of the follicular variant of the PC had signs of invasion and were significantly more often observed (P < 0.01) compared with the classical and oxyphilic cell variants. The BRAF V600E mutation was observed both in tumors with metastasis to the regional lymph nodes (55.0 %) and in tumors without metastases (37.5 %), with no significant difference. Conclusions. The presence of the BRAF V600E mutation is a diagnostic marker for papillary thyroid carcinoma, and its detection confirms the presence of malignancy. BRAF positive carcinomas were in 46.5 % of cases. The combination of BRAF-negative and the cytology of groups V and VI by Bethesda may indicate about a follicular variant of PTC. An increase in the number of molecular genetic markers in the preoperative diagnosis of thyroid cancer can significantly improve the quality of diagnosis and surgical treatment.